The Obstacles Facing the Backyard Chicken Breeders in Some Villages of Bamerny Sub-District of Duhok Governorate - Ismael Taha; Hashim Murad; Salah Amin; Roaa hamid (مجلة جامعة كركوك للعلوم الزراعية, 2022)
The study was conducted in the Bamerny sub-district of Duhok Governorate to identify the extentobstacles facing backyard chicken breeders. Sixty chicken breeders were comprehensive selected.Questionnaire of three fields of obstacles facing chicken breeders: production, marketing, anddiseases, covering 16 obstacles was prepared. The results showed that (60%) of the respondentsmentioned that the obstacles they face are medium and large size obstacles. The results alsoindicate that the obstacle (high cost of transportation) ranked first among (16) with an average of(4.017), while the obstacle (inappropriate environmental conditions) came in the last rank, with anaverage of (1.59). The results also shows that most of the respondents were younger than 30 years(46.6%) and had been educated beyond Primary and diploma levels (25%). As clear most of therespondents (70%) had experience in chicken production was ten years and more. The resultsillustrate that for most of the respondents (58.3%) their chicken houses capacity was between 20-52 birds. The results of the research showed that the level of Sources of information used inchickens’ production (53.3%) degrees, in a small group. problems and obstacles facing theindividual backyard chicken breeders can be addressed a supported through government agencies,active extension services, and stakeholders to solve their problems, access relevant information,and uptake improved management techniques.